Hajhamed’s methodological reflections on Islamizing Social Sciences - Shuriye, Abdi Omar (2007)
The idea of this paper initially came when I went through the available literature on Hajhamed, particularly I decided to initiate a work in a form of book. This paper stands as the preliminary component of that work. The main aim here is to reinforce the methodological contributions of Hajhamed in the process of Islamizing social sciences.